PENGARUH HALAL AWARENESS DAN ISLAMIC BRANDING TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN AMDK MAAQO MASYARAKAT MUSLIM JOMBANG - Amalia, Nur Halizatul; Nurafini, Fira (Jurnal Ekonomika dan Bisnis Islam, 2024)
Consumer demand for halal food and beverages is increasing as the Muslim population Consumer demand for halal food and beverage needs is increasing as the Muslim population grows. Muslim communities who have knowledge about halal play an important role in the demand for halal products. So that makes business people have to consider halal aspects in their products. This study aims to analyze the effect of halal awareness and islamic branding on customer satisfaction through purchasing decisions for Maaqo brand bottled drinking water by Muslim communities in Jombang Regency. The data were analyzed using the SEM-PLS technique. The data used is primary data through distributing questionnaires. The research sample amounted to 130 respondents with certain criteria using purposive sampling technique. The results of this study indicate that halal awareness affects purchasing decisions. Halal awareness has no effect on customer satisfaction. Islamic branding affects purchasing decisions. Islamic branding has no effect on customer satisfaction. Purchasing decisions affect customer satisfaction. Halal awareness affects customer satisfaction through purchasing decisions. Islamic branding affects customer satisfaction through purchasing decisions for Maaqo brand bottled drinking water products. These results indicate that the Muslim community of Jombang district makes halal awareness and Islamic branding a determinant of customer satisfaction when through purchasing decisions for bottled water products.